Labour Exploitation in Enola Holmes 2: A Marxist Analysis - Novaya Salsabila; Pratiwi Retnaningdyah (Anaphora : Journal of Language, Literary, and Cultural Studies, 2026)
Enola Holmes 2 (2022) depicts Enola’s battles as a young detective and the harsh realities of the exploitation of the match factory workers in Victorian times. The aim of this study is to analyse the kinds of labour exploitation and class consciousness represented in the film. The current qualitative research uses script analysis with the theory of hegemony (Gramsci), repressive and ideological state apparatus (Althusser) and class consciousness (Marx and Engels). The findings indicate that exploitation takes place in three main forms: the normalisation of hazardous working conditions; the manipulation of information and propaganda by capitalist; and violence perpetrated by the state apparatus (the police), which acts as an instrument of the bourgeoisie. The oppression of this kind within the system created class consciousness among workers and resulted in collective strikes being employed as a method of political action. These strikes simultaneously challenged capitalist hegemony, altered relations of unequal production, and made workers active political agents. The research indicates film is not only for fun; it is an effective instrument for social critics.